Highly fluorescent single crystals of a 4-ethoxy-1, 3-thiazole. (February 2018) - Habenicht, Stefanie H.; Kupfer, Stephan; Nowotny, Jürgen; Schramm, Stefan; Weiß, Dieter; Beckert, Rainer; Görls, Helmar
Abstract: 4-Ethoxy-2-(pyridin-2-yl)-5-(3, 4, 5-trimethoxyphenyl)thiazole (EPTT ) was prepared in a four-step synthetic protocol. Column shaped single crystals of EPTT were obtained from a saturated EtOH solution. Both single crystals and a THF solution of EPTT were investigated in terms of their photophysical properties and electronic structure. The crystals showed very intense fluorescence upon photoexcitation as well as a red shifted emission maximum compared to a THF solution of EPTT (single crystals: λem = 523 nm, ΦFL = 0.82, THF solution λem = 477 nm, ΦFL = 0.67). Quantum chemical methods were then employed to unravel the underlying fundamental transitions and explain the experimental results. Calculations for a small dye cluster modeled after the x-ray crystal structure predicted three dark intermolecular CT states, S1 -S3, below the intramolecular CT state (S4 ) for EPTT in the crystalline state. Photoexcitation and subsequent relaxation along the excited states relaxation pathways may populate the low-lying dark intermolecular CT states, which in consequence leads to an exciton moving along the stacked dyes in the crystal. This finding explains the significantly enhanced red-shift of the solid-state fluorescence of EPTT compared to the dissolved dye. Graphical abstract: Highlights: A new 4-alkoxythiazole fluorophore EPTT was synthesized. EPTT exhibits sky-blue fluorescence (477 nm) with 67% quantum yield in THF. EPTT shows enhanced and red-shifted fluorescence (523 nm, 82% quantum yield). Calculations revealed three dark intramolecular CT states in the crystalline state. Population of the dark CT states explains the red-shifted solid state emission.